Silence and sacrifice : family stories of care and the limits of love in Vietnam - Shohet, Merav, 1976- (University of California Press, 2021)
"How do families hold together when turbulent forces tear them apart? Silence and Sacrifice explores what happens to generations of kin who survived anti-imperial and civil wars in Vietnam, only to be confronted with postcolonial transitions to communism and market-friendly late socialism. In recounting vivid family experiences of conflict, love, and loss, Shohet revises canonical theories of sacrifice as blood-filled religious rituals or patriotic acts. Motivated by enduring Vietnamese virtues of asymmetrical reciprocity and tình cảm (love and material care), a myriad of domestic sacrifices-especially by women-precariously knot family members together by silencing suffering and naturalizing gender and other hierarchies. Rethinking ordinary ethics, this intimate ethnography reveals how quotidian acts of sacrifice help family members forge a sense of continuity in the face of massive political and economic upheavals"--